Anabolic-androgenic steroids: procurement and administration practices of doping athletes - Fink, J.; Schoenfeld, B. J.; Hackney, A. C.; Matsumoto, M.; Maekawa, T.; Nakazato, K.; Horie, S. (The Physician and Sportsmedicine, 2019)
Performance enhancing substances are becoming increasingly popular amongst bodybuilders and people who want to enhance their physiques. However, due to the rise of the Internet and laws prohibiting sales of these substances without prescription, the route of procurement and administration practices have become more and more dangerous. Prior to the mid-1970`s, anabolic steroids were not regulated and easily available from physicians and pharmacies in several countries. In 1990, the United States enacted the Anabolic Steroid Control Act, leading to the proliferation of black markets and underground laboratories. The shift from pharmacy to underground online sites for the procurement of anabolic steroids led to an increase of fake products with low purity and the ability to potentially endanger the health of anabolic steroid users. Underground laboratories emerged both locally and in countries with lax legal regulations. `Anabolic steroid tourism` and large networks of online resellers emerged, leading to the banalisation of the illegal procurement of anabolic steroids. Furthermore, the increase of anecdotal information spreading on the internet among anabolic steroid user forums nourishes the rampant misinformation and dangerous practices that currently exist. The dosages and ways of administration recommended on these forums can be false and misleading to those who lack a medical background and cannot go to their physician to seek advice because of the fear of repercussions. This review aims to elucidate and describe current practices of the anabolic-androgenic steroids black market and draw attention to potential dangers for users.